Evaluación de la participación ciudadana en la gestión pública del Gobierno Autónomo Descentralizado de Tosagua y Junín periodo 2016-2020 - Alvarado Quiroz, Celia Arlene (2022)
This work evaluates citizen participation in public policy decisions of the cantonal GADsin Tosagua and Junín, Manabí province, in the period 2016-2020. The research was non-experimental, exploratory and under a mixed approach, which allowed the application of both quantitative and qualitative methodologies. The study was carried out in three phases: in the first one, the citizen participation mechanisms used by the GADs in Tosagua and Junín were identified; in the second one, the influence exerted by these mechanisms in public management during the period under study was analyzed; and, in the third one, a proposal for evaluating citizen participation in public policy decisions of the GAD under study was designed. These phases were carried out through the documentary review of the material obtained from each GAD, the application of surveys to the subjects selected as a sample and interviews with 4 individuals who work in the mayor's offices and represent the management of citizen participation in the GADs. The statistical results and qualitative findings allowed revealing the shortcomings found in the application of citizen participation mechanisms, which led to the conclusion that these have not been used properly and that only the application of some is promoted, such as the approval of planning the budget and accountability. The others are not applied in their entirety while those that are activated are made with weaknesses that prevent the empowerment of the participatory processes' citizen. Finally, an improvement proposal is designed and presented to solve the reality detected.